Vital capacity exercising device for pneumology department - CHEN SHUIQIN; OTHER INVENTORS HAVE WAIVED THE RIGHT TO BE MENTIONED (2022)
The utility model belongs to the technical field of medical instruments, particularly relates to a vital capacity exercising device for the pneumology department, and aims at solving the problems that an existing vital capacity exercising device is still inconvenient in overall adjustment and poor in use experience, the following scheme is provided: the vital capacity exercising device comprises a training box which is made of aluminum alloy with an open rectangular structure; anti-skid rubber adheres to the bottom end of the training box, the upper end face of the training box is connected with a rectangular sealing cover through screws, two round open holes are formed in the surface of the rectangular sealing cover in a penetrating mode, and a connecting pipe is placed in the training box. And stable use experience can be brought to a user. 本实用新型属于医疗器材技术领域，尤其是一种呼吸科用肺活量锻炼装置，针对现有肺活量锻炼装置依然存在着整体调节不便，倒是使用体验不佳的问题，现提出如下方案，其包括一训练箱，所述训练箱采用敞口矩形结构的铝合金，所述训练箱的底端粘附有防滑橡胶，所述训练箱的上端面通过螺钉连接有矩形封盖，所述矩形封盖的表面贯穿开设有两个圆形开孔，一连接管放置在所述